Fostering diagnostic competence in prospective mathematics elementary teachers through epistemic activities - Volkmer, Jan Philipp; Eichler, Andreas; Rathgeb-Schnierer, Elisabeth (Frontiers in Psychology, 2023)
Research on fostering teachers' diagnostic competence and thinking has become increasingly important. To this end, research has already identified several aspects of effective fostering of teachers' diagnostic competence. One of the aspects is assignment of the role as a teacher in interventions but, so far, assignment of the role of student has hardly been considered. Based on a model of the diagnostic thinking process, this paper operationalizes the role of the student by solving specific tasks and the role of the teacher by analyzing student solutions. Furthermore, based on previous research, it is assumed that assigning both roles is effective in promoting diagnostic competence. The following research addresses the development of 137 prospective teachers' diagnostic thinking in an experimental pre-post-test study with four treatment conditions, which vary prospective teachers' working with tasks and students' solutions to those tasks. The quantitative results show that a treatment integrating focus on tasks and students' solutions is equally as effective as a treatment focusing solely on students' solutions, and also that a treatment focusing solely on tasks has no effect.